IMPROVING MARKETING PERFORMANCE OF THE INFORMATION TECHNOLOGY INDUSTRY - Wahid, Ayi; Afifah, Vivi; Saroso, Dana Santoso (LPPM Nusa Mandiri, 2022)
The marketing performance of the information technology industry in DKI Jakarta was still low, allegedly due to customer focus, cross-functional coordination, and relatively low organizational capability. The purpose of this research was to determine and analyze the effect of customer focus, cross-functional coordination, and organizational capability partially or simultaneously on marketing performance. Descriptive and explanatory survey methods, the method used in this research with a sample size of 200 respondents, while the data analysis method used a structural equation model. The results showed that customer focus, cross-functional coordination, and organizational capability partially or simultaneously had a positive and significant effect on marketing performance with a contribution of 76%. Cross-functional coordination was partially the most dominant variable influencing marketing performance. The results of other studies show that the most dominant dimension in measuring customer focus was the service process dimension. While product development and marketing program preparation are the dominant dimensions in measuring cross-functional coordination, interpersonal skills are the dominant dimensions in measuring organizational capability, and profitability is the most dominant dimension in measuring marketing performance..